ANALISIS PERBANDINGAN ANTARA BIAYA OPERASIONAL KENDARAAN (BOK) DI JALAN ARTERI PRIMER DENGAN RENCANA JALAN TOL RUAS : UNGARAN - SALATIGA - Rendy Augusta Wirayoga; Danang Setiyo Cipto Saputro; Djoko Purwanto; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Semarang is one of the big cities, where many centers of economic, political, socio-cultural and educational center. The existence attractive to residents outside of Semarang to travel to Semarang. Most Salatiga’s residents doing trip - roundtrip to the Semarang city. However, the operation conditions of public transportation that led to and leaving Semarang still not up and there are a few obstacles along the way such as markets, factories and other activities that disrupt the trip. This transport problems will cause a variety of negative effects, such as lost time due to the long trip and the increase in Vehicle Operating Costs (VOC) to existing roads, so that the government develop a national road network in particular in areas of Java such as Trans Java Toll road construction Semarang - Solo segment. The purpose of this evaluation is to analyze the velocity space (space mean speed) and the Vehicle Operating Costs comparison between existing roads and toll roads segment Ungaran - Salatiga. Vehicle Operating Costs (VOC) using the Pacific Consultants International (PCI) formula. Data that obtained from the survey results for the velocity space (space mean speed) toward Ungaran - Salatiga for each vehicle and departure times both morning and afternoon, for the morning bus speeds faster 1.55 km / h of speed during the day is 31.14 km / h; 2 axle trucks during the day faster 4.67 km / h of speed in the morning is 30.76 km / h; as daytime tuk 3 faster 1.37 km / h from speed in the morning is 27.05 km / h; while the direction of Salatiga - Ungaran for the bus in the morning faster 1.21 km / h of speed during the day is 36.36 km / h; 2 axle trucks during the day more fast 3.77 km / h of speed in the morning is 34.29 km / hr; 3 axle truck in the morning faster 3.09 km / h of speed during the day is 26.81 km / h. The average speed for the Toll Road is taken based on a minimum speed of 60 km / h. The results of the comparison vehicle operating cost (VOC), it costs when crossing the Toll road is more economical when compared to the existing road. Where is the economic value of the vehicle in the morning for the bus is more efficient to IDR 37.132,38 (27.19%); 2 axle trucks more efficient IDR 32,802.99 (30.17%); and 3 axle trucks more efficient IDR 22,842.59 (13.58%). While in the afternoon, when crossing the Toll road for the bus will be more efficient IDR 39,564.97 (28.47%); for 2 axle trucks more efficient IDR 26,220.25 (25.67%); while for 3 axle trucks would be more efficient IDR 23,083.17 (13.70%).